Performance and cost of applied nucleation versus high-diversity plantations for tropical forest restoration - Bechara, Fernando Campanha; Trentin, Bruna Elisa [UNESP]; Engel, Vera Lex [UNESP]; Estevan, Daniela Aparecida; Ticktin, Tamara (Elsevier B.V., 2021)
How to best restore highly diverse tropical forests to deliver an affordable and effective legacy of biodiversity remains an ecological dilemma. We investigated both vegetation recovery and financial outcomes of forest restoration in applied nucleation and high-diversity plantation plots in the Atlantic forest of Brazil. We used a randomized block design with four replicates (40 ? 54 m plots) for each of the two restoration treatments and a control (natural regeneration). After six years, we sampled 50% of the restored area and calculated all labor and input costs associated with both restoration establishment and maintenance. Overstory basal area, species richness and species diversity were highest in plantation and lowest in control plots. Understory density was also higher in plantation plots but density of shrubs and vines was higher in nucleation and control plots. There were no differences in understory species diversity or richness across treatments. When considering only recruited individuals, overstory density and basal area, and species richness in both over and understory was highest in nucleation plots. In comparison to plantation plots, the overstory composition of nucleation plots was more similar to control plots and there was greater variability across plots. The total cost of restoration was up to 34% cheaper in nucleation (US$ 4654.09 ha-1) than in the high-diversity plantations (US$ 7038.05 ha-1). While high-diversity plantation restoration is currently the most widespread and prevalent approach, applied nucleation appears to offer an intermediate level of recovery speed and cost, and can be a valuable strategy that can strike a balance between passive and active restoration.
Keywords: Subtropical forest; Recovery; Succession; Natural regeneration; Brazil; Atlantic forest